SCN5A mutations and the role of genetic background in the pathophysiology of Brugada syndrome. (3rd October 2022) - Probst, V; Ribouleau, G; Geoffroy, O; Mabo, P; Mansourati, J; Pasquie, J L; Babuty, D; Al Arnaout, A; Petit, B; Billon, O; Thollet, A; Sacher, F; et al.
Abstract: Background: Mutations in SCN5A are identified in approximately 20% to 30% of probands affected by Brugada syndrome (BrS). However, in familial studies, the relationship between SCN5A mutations and BrS remains poorly understood. The aim of this study was to investigate the association of SCN5A mutations and BrS in a group of large genotyped families. Methods: Families were included if at least 3 family members were carriers of the SCN5A mutation, which was identified in the proband. Families were recruited from 12 tertiary centers in France between 1995 and 2020. Type 1 ST elevation was defined by ≥2 mm J-point elevation with coved ST segment and negative T wave. Results: Forty-nine large families composed of 600 members including 304 mutation carriers (51%) were studied. The signature type I ECG was present in 160 mutation carriers (BrS-ECG+; 53%). In 42 families, we found 33 individuals affected by BrS but with a negative genotype (mutation-negative BrS-ECG+). Among them, 5 patients have an ECG suggestive of BrS but without the complete signature type I ECG. Among these 33 mutation-negative BrS-ECG+ individuals, 3 (9%), belonging to 3 different families, had a spontaneous type I ECG, whereas 28 had a type I ECG only after the administration of sodium channel blockers. Three of these 33 individuals (9%) had also experienced syncope. Mutation carriers had, on average, longer PR (190±36 ms vs 154±29 ms, p<0.0001) and QRS (107±19 vs 92±29 ms, p<0.0001) intervals than noncarriers, demonstrating that these mutations exerted functional effects. Conclusions: Our results suggest that SCN5A mutations are not directly causal to the occurrence of a BrS-ECG+ and that genetic background may play a powerful role in the pathophysiology of BrS. These findings are consistent with the notion that the pathophysiology of BrS includes various elements beyond mutant sodium channels. Funding Acknowledgement: Type of funding sources: None.